PERANG RUSIA, COVID 19 DAN REVITALISASI AGRIKULTURAL: MENIMBANG GAGASAN POLITIK PERTANIAN SJAFRUDDIN PRAWIRANEGARA (1911-1989) - Hasan Mustapa; Siti Kania (UIN Mataram, 2022)
Abstract In the midst of the ongoing Covid 19 pandemic, Russia's invasion of Ukraine poses a threat to global food security, including Indonesia. Faced with this threat, the management of national food politics is still skewed by conglomerates and oligarchs, resulting in far from democratic national agricultural policies. Agricultural revitalization efforts are one way to deal with this situation. This article seeks to understand how Sjafruddin Prawiranegara (1911-1989), an Indonesian Islamic political thinker, responded to the agricultural development process in critical situations such as war and, more recently, the Covid-19 outbreak. According to him, the agricultural industry can be revitalized in two ways: macro and micro. At the macro level, through the evaluation of rice import policies, food-based economic political orientation, and agricultural industry revitalization. On a micro level, rice prices can be stabilized by providing farmer credit, reactivating agricultural cooperatives, and facilitating access to food distribution. Keywords: Russian Invasion, Covid-19, Food Security, Agricultural Revitalization Abstrak Invasi Rusia ke Ukraina di tengah Pandemi Covid 19 yang masih berlangsung mengancam ketahanan pangan global, termasuk Indonesia. Menghadapi ancaman itu, penanganan pengelolaan politik pangan nasional masih bias konglomerasi dan oligarki sehingga kebijakan pertanian nasional jauh dari demokratis. Keadaan ini perlu disiasati salah satunya melalui upaya revitalisasi agrikultural. Artikel ini ingin mengetahui bagaimana respons Sjafruddin Prawiranegara (1911-1989), seorang pemikir politik Islam Indonesia, menanggapi proses pembangunan pertanian dalam situasi genting, di antaranya perang, dan dalam konteks kekinian; wabah Covid-19. Baginya, kebangkitan industri pertanian bisa didorong melalui dua cara, makro dan mikro. Secara makro melalui evaluasi kebijakan impor beras, orientasi politik ekonomi berbasis pangan serta revitalisasi industri pertanian. Secara mikro melalui pemberian kredit petani, reaktivasi koperasi pertanian serta mempermudah akses distribusi pangan guna stabilisasi harga beras. Kata Kunci: Invasi Rusia, Covid-19, Ketahanan Pangan, Revitalisasi Agrikultural